Use of live oocyst vaccine in the control of turkey coccidiosis: Effect on performance and intestinal morphology - Milbradt, E. L. [UNESP]; Mendes, Ariel Antonio [UNESP]; Ferreira, J. G. [UNESP]; Paz, Ibiara Correia de Lima Almeida [UNESP]; Martins, M. B. [UNESP]; Sanfelice, C. [UNESP]; Fernandes, B. C. [UNESP]; Okamoto, Adriano Sakai [UNESP] (Oxford University Press, 2014)
An experiment was conducted to determine the effects of different coccidiosis-preventing programs on performance and intestinal morphology of commercial turkeys. Three hundred fifteen1-d-old female commercial cross turkey poults (British United Turkeys, BUT Big 9) were distributed into 3 treatments with 5 replicates of 21 birds each. Three programs were evaluated from 1 to 70 d of age, where program 1 had no anticoccidial drug and no vaccination against coccidiosis; program 2 had an anticoccidial drug (maduramycin 1%, 5 ppm); and program 3 had a vaccination (commercial vaccine, 4 species of Eimeria). All the groups were challenged with a dose of oocysts sporulated (20,000/bird) of 2 species of Eimeria at 21 d of age. In the growing phase (d 0-28), BW, BW gain, and FCR were significantly greater in treated groups compared with control group. In the fattening phase, the performance was not affected by treatments. Treatments and coccidiosis challenge had no significant effects on intestinal villus height. These observations support other reports that confirm live oocyst vaccination can be used effectively as a preventive against avian coccidiosis in commercially reared turkeys.
Keywords: anticoccidial drug; Eimeria; polymerase chain reaction